SIGNIFICANCE OF SURFACE AREA OF ANODE IN GENERATION OF ELECTRICITY THROUGH MICROBIAL FUEL CELL FED WITH ANAEROBICALLY DIGESTED DISTILLERY WASTEWATER - ANIMESH S. DEVAL,; ASHOK M. BHAGWAT,; ANIL K. DIKSHIT, (International Journal of Pharma and Bio Sciences, 2014)
Microbial fuel cells (MFCs) convert chemical energy into electrical energy using microorganisms. Various factors influence electricity generation by MFC. Surface areas of cathode and anode have been reported as significant factors affecting the performance of MFC. Hence, in the present study, the above mentioned factors were investigated for understanding their influence on generation of electricity. It was observed that the surface area of cathode did enhance the energy generation but only up to a certain limit (18.42 cm2). However, surface area of anode was found to be more important and critical in increase the capacity and sustainability of the MFC system. Hence, it can be concluded that in an MFC system, bacteria are solely responsible for generation of electrons and thus, electricity. Providing large surface area for bacterial growth at anode would thus be a key parameter to enhance the electricity generation.